Original enlightenment and the transformation of medieval Japanese Buddhism - Stone, Jacqueline Ilyse (Studies in East Asian Buddhism, 1999)
"Original enlightenment thought (hongaku shiso) dominated Buddhist intellectual circles throughout Japan's medieval period. Enlightenment, this discourse claims, is neither a goal to be achieved nor a potential to be realized but the true status of all things."--Jacket